2013
DOI: 10.1136/bmjopen-2013-003453
|View full text |Cite
|
Sign up to set email alerts
|

What are effective approaches to increasing rates of organ donor registration among ethnic minority populations: a systematic review

Abstract: ObjectivesTo identify effective interventions to increase organ donor registration and improve knowledge about organ donation among ethnic minorities in North America and the UK.DesignSystematic review.Data SourcesMEDLINE, EMBASE, PsycINFO, CINAHL and Cochrane Central searched up to November 2012, together with four trials databases and the grey literature.Review methodsA systematic search followed by assessment of eligibility and quality. An interpretive and thematic approach to synthesis was undertaken. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 32 publications
(33 reference statements)
3
41
0
Order By: Relevance
“…A comparison of six one‐minute videos (four with personal narratives, one with donation information but without personal narrative, and one unrelated to organ donation) found no significant difference among the videos in the number of attempts by participants to learn more about donation or to register to donate organs . However, a systematic review of different interventions that were successful in increasing consent for organ donation identified a “strong interpersonal component” as an important characteristic of successful change . To our knowledge, there has not been a study demonstrating the effectiveness of one organ donation video type over another in increasing willingness to consent for donation.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of six one‐minute videos (four with personal narratives, one with donation information but without personal narrative, and one unrelated to organ donation) found no significant difference among the videos in the number of attempts by participants to learn more about donation or to register to donate organs . However, a systematic review of different interventions that were successful in increasing consent for organ donation identified a “strong interpersonal component” as an important characteristic of successful change . To our knowledge, there has not been a study demonstrating the effectiveness of one organ donation video type over another in increasing willingness to consent for donation.…”
Section: Introductionmentioning
confidence: 99%
“…Second, although both organ donor designation and family approval for the decision to remove organs are needed in Japan, the primary outcome in our study was simply organ donor designation. However, the primary endpoint of many previous studies was organ donor registration or designation, as is the case with our study and 3 weeks seemed to be too short for students to obtain family approval. Third, contamination occurred in about half of the students in both groups.…”
Section: Discussionmentioning
confidence: 85%
“…Two systematic reviews have shown that education on organ donation and transplantation effectively influenced participants' knowledge, attitudes, and behavior . However, little is known about the effect of education programs on changing attitudes and behaviors of participants and their families toward deceased organ donation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last three decades, colleagues have studied ways to influence and effectively alter the modifiable barriers associated with organ donation among ethnic minority groups and African Americans in particular (9). Studies indicate that African Americans tend to be less knowledgeable about donation and/or transplantation than other racial/ethnic groups (10).…”
mentioning
confidence: 99%